Not This, Not That:* Maurice Blanchot and Poststructuralism†. Issue 1 (2nd January 2016) - Singh, Rustam
Abstract : Far from being a precursor of poststructuralism, Maurice Blanchot was located at the very core of this movement. This becomes clear from Blanchot's views on language, on the subject, on the Book or the Work, and on the fragmentary. At the same time, through his notion of neuter or the neutral—a notion which is central in his work and also in poststructuralist discourse—Blanchot went further than certain elements of poststructuralism, especially beyond Derrida's notion of différance .